Exploration of behavior, forms and applications of microbial material - Ng, Audrey (2019)
This research project presents the exploration of behavior, forms and applications of microbial material which is an environmentally friendly alternative material. Cross-disciplinary collaborations between art and science to create awareness and a head start of the eco-movement through art and products to rethink the quality of our daily consumptions. Microbial cellulose, cultured by Kombucha will be used in this study. At present, the flat grown microbial material is generally made into a wearable through conventional cutting and sewing. However, this thesis research aims to make microbial material into a finer and unique quality of material and further identify the gaps that need to be explored. The research will first discover and manipulates its properties with the goal of making it a better alternative material in the fashion and product design field. This research sets out to investigate possible production techniques available mainly to artists and designers. Therefore, the research approach will be mainly covering several studies on the behavior of Kombucha cellulose to further handle its growing techniques and create potential 2D and 3D structure forms and manipulations. Lastly, through the combination of different aspects of experimentations on Kombucha cellulose, several artifacts have been created to explain and expand the application benefits of this microbial material based on its natural process. This research has expanded the possibilities to manipulate the growing patterns of Kombucha cellulose into different outcomes to enhance its performance and functionality. Through designed experimentations, Kombucha cellulose is able to overcome its natural growth behavior and turn the 2D flat layer of Kombucha cellulose into a 3D structure artefacts.